Strategi Dakwah Reflektif Fahruddin Faiz (Membumikan Filsafat dalam Kajian Islam Kontemporer) - Hari Rahman Hakim; Aisah; Firman Saputra; Yoyon Sahroni; Deden Ibnu Akil; Siti Zakiah (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study aims to analyze Fahruddin Faiz’s reflective dakwah strategy in grounding Islamic philosophy within contemporary Islamic discourse. Employing a qualitative approach with a case study design, this research conducts content analysis of sixty episodes of “Ngaji Filsafat” as well as Faiz’s published works. The findings reveal that Faiz’s reflective dakwah is constructed through dialogical–interrogative methods, systematic philosophical argumentation, contextualization of classical Islamic philosophical concepts, and conceptual simplification that renders abstract ideas accessible to wider audiences. The study also identifies a strong transformative dimension that shifts religious understanding from merely knowing to being, facilitated through critical consciousness, paradigm transformation, and the integration of reflection and praxis. An integrative epistemological framework that synthesizes revelation, reason, and existential experience forms the foundation of this approach. Furthermore, the effectiveness of Faiz’s dakwah is strengthened by the use of multi-platform digital communication, enabling broad and diverse audience engagement. Overall, the findings confirm that reflective-philosophical dakwah represents a contemporary, moderate, and transformative model capable of addressing the intellectual and spiritual needs of modern Muslim society.